FROM CONSUMPTION TO CULTURAL PRACTICES. AN APPROACH FROM BIOGRAPHICAL ARTICULATIONS - Aliano, Nicolás; Moguillansky, Marina (Centro de Investigaciones y Estudios sobre Cultura y Sociedad, 2017)
The article inquires how the subjects relate to culture through practices and consumptions inscribed in diverse sociability relations –recommendations, suggestions, company– which are combined and intertwined to  form complex cultural repertories. A construction of short cultural biographies was carried out, based on semi-structured interviews with a set of subjects selected through theoretical criteria. We selected some cases from the group of interviewees, to build profiles of cultural practitioners. The analysis concludes with a characterization of the cultural practices registered as “social”, “reflexive”, and “interconnected”, and aims to describe an emergent process of singularization of cultural trajectories of the subjects and the constitution of plural and heterogeneous preference profiles.